Saliva sebagai Media Diagnosis untuk Deteksi Keganasan - Dian Yosi Arinawati; Aprilinda Widyawati (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2022)
Human saliva is a potential diagnostic fluid where most of changes in the body can be reflected in saliva and it considered a "mirror of the body". Currently, salivary biomarkers help in the detection of oral cancer, dental caries, periodontal disease, diabetes, breast cancer, and lung cancer. Saliva like others body liquid in human body such as urine and blood contain tumour derived biomarkers i.e DNA, asam amino, cells and vesicles which shed via bloodstream and secreted through salivary gland. Salivary diagnostic is a growing dynamic field utilizing nanotechnology and molecular diagnostics to aid in the diagnosis of oral and systemic diseases. The purpose of this review is to determine saliva as a diagnostic medium through various its biomarkers to detect malignancies in the body. The use of saliva as a medium for molecular diagnosis has the advantage of being sensitive, specific, can be used as a screening medium in diagnosing and staging, therefore usefull for early detection of malignancy, for example Oral Squamous Cell Carcinoma can be seen in three levels, changes in cellular DNA, altered mRNA transcripts, altered protein levels (intracellular or extracellular). It can also detect other cancers such as Salivary Gland Cancer, and even in parts of the body far from the oral cavity such as Lung Cancer, Pancreatic Cancer, Breast Cancer. It can be concluded that saliva can be used as a non-invasive diagnostic medium to detect various oral and systemic malignancies.